Gemeinsame Verantwortlichkeit unter der DSGVO Unter besonderer Berücksichtigung von Internetsachverhalten - Radtke, Tristan (Schriften zum Medien- und Informationsrecht, 2021)
Cooperation in the processing of personal data is particularly relevant on the Internet when, for example, third party content is embedded. The General Data Protection Regulation stipulates Joint Control as a technology-neutral concept to potentially cover such constellations (Art. 4 No. 7 GDPR, Art. 26 GDPR). The author discusses systematically the relevant case law of the European Court of Justice (Wirtschaftsakademie, Jehovah's Witnesses and Fashion ID), elaborates the preconditions of Joint Control and puts the legal figure in the context of the GDPR with its legal consequences such as claims for damages, supervisory measures and the internal relationship of Joint Controllers.